Methods and Results of Experimental Studies on The Indicators of Combined Fertilizers - Аbdumalikov Ulugbek (American Journal of Biodiversity, 2026)
This article presents a fertilizer device of a combined unit that distributes organic fertilizers over the surface of a field in the form of a strip and forms a pile above it. The device studied the diameter of the auger of fertilizer blades, the number of revolutions, the installation angle of the blades on the shaft, as well as the influence of the installation angle of the blades on the shaft. The results of experimental studies to determine the uneven distribution of fertilizer application rates according to the movement of the unit are determined.